Take-out food frequency was associated with energy intake among mothers of young children in urban slum area in North Jakarta - Luh Ade Ari Wiradnyani; Fitya Safira Birahmatika; Dian Novita Chandra (World Nutrition Journal, 2021)
Introduction: Inadequate energy intake was prevalent among women of reproductive age, which may contribute to poor diet. Having great concern towards health and nutrition may play a role in shaping eating habit and food-related behavior to achieve a healthy diet. This study aims to examine the association between health concern and energy intake, while considering other factors such as cooking frequency and having food away from home.Methods: This cross-sectional study was carried out in an urban slum area in Jakarta, involving 233 mothers of young children through consecutive sampling. Data was collected through interview using structured questionnaire, including 2x24-hour dietary recall. All statistical analysis was performed using SPSS Version 20.Results: Energy intake of most subjects did not meet the recommendation. There was no significant correlation between health concern measured by General Health Interest Scale and energy intake. The frequency of having take-out food was a significant predictor of the energy intake. Additionally, a significant negative correlation between health concern and having take-out food was found.Conclusion: Having take-out food was associated with energy intake. Provision of health and nutrition information in the food stores might help to increase health concern to shape a healthier diet. Thus, a collaborative effort targeting both food sellers and customers is essential.